DRAMA OF AVGOUSTIN VOLOSHIN IS «MAROUSYA VERHOVINCA»: LITERARY FUNDAMENTAL PRINCIPLE AND STAGE INTERPRETATION - Rebryk, N. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
"Marousya Verhovinca", which causes interest of not only narrow circle of researchers but also modern spectator, is explored in the article to the feature of conflicts and characters of drama of Avgoustin Voloshin.